Teacher-Students Power Relation in Online Class Interactions in the Higher Education Context - Laser Romios; Sulastri Manurung (Universitas PGRI Yogyakarta, 2026)
As online class during the Covid-19 pandemic was mandatory, teaching methods changed and no-human touch was involved, causing fewer social dynamics and interactions. Hence, it is interesting to investigate how a lecturer and students dealt with it. This study aimed to investigate the power relation between a lecturer and his students in a tertiary level education in a particular course of a doctoral degree majoring English Education. The study employed qualitative research with a case method to explore how teacher and students exercised power in online class interactions from January-May 2022. Data were obtained from a recording of zoom meetings involving a male lecturer and 20 doctoral students in a state university in Bandung, Indonesia. Online class verbal and nonverbal interactions were transcribed to describe, interpret, and analyze the teacher-student discursive practices. Analysis of the data was done through the three stages of critical discourse analysis by Fairclough, including description, interpretation, and explanation. In particular, the study employed the systemic functional linguistics by Eggins and Halliday to discuss mood type and to understand the semantic system of speech function and mood employed by the teacher and students. Based on the analysis of three episodes, the study shows that the lecturer did not dominate the classroom, suggesting the power relation was equal. Thus, students found it easy to demonstrate their ideas and opinions during classroom activities.Keywords: Power Relations; systemic functional linguistics; English Education; Tertiary Education